1995
DOI: 10.1111/j.1467-8381.1995.tb00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Tax Elasticities and the Impact of Discretionary Tax Measures on Government Revenue in Papua New Guinea, 1975–92

Abstract: This paper evaluates tax elasticities and the impact of discretionary tax measures on government revenue in Papua New Guinea (PNG) using a dynamic macroeconometric model of taxation which captures the interaction between GDP, individual tax systems and individual tax revenues and bases. Our findings show that economic growth and discretionary tax changes have both been effective in mobilizing additional tax revenue. However, the responsiveness of the individual tax system reflected base‐to‐GDP elasticity excep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(1 reference statement)
0
1
0
Order By: Relevance
“…The study also looked at the relationship between the tax reform and revenue performance. According to Kusi (1998), the tax reform has been successful in increasing tax revenue, enhancing the effectiveness of tax administration, and enhancing systemic equality. As there isn't much research on corporate matters related to these activities in the context of Bangladesh, Chowdhury and Hossain's 2019 study is an attempt to evaluate such projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study also looked at the relationship between the tax reform and revenue performance. According to Kusi (1998), the tax reform has been successful in increasing tax revenue, enhancing the effectiveness of tax administration, and enhancing systemic equality. As there isn't much research on corporate matters related to these activities in the context of Bangladesh, Chowdhury and Hossain's 2019 study is an attempt to evaluate such projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Otherwise, the upgrading of NBR would be a far cry. Kusi (1998) in his study has examined the links between the tax reform and revenue performance and found that the tax reform has had a significant positive influence on the productivity of both the personal tax revenue and the overall tax system. The tax reform has succeeded in terms of generating more tax revenue, augmenting the efficiency of the tax administration, and improving equity in the tax system.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Customs has been established as a semi-autonomous government agency in Ghana and Ethiopia. Established in 1839, Ghana's Customs, Excise and Preventive Service (CEPS) was transformed under PNDC Law 144 into a semi-autonomous government agency outside the civil service in 1986 (Kusi 1998;Ghana Customs 2008b). The first customs law was passed under colonial rule in 1855 (Terkper 1995).…”
Section: B Customs As a Semi-autonomous Agencymentioning
confidence: 99%
“…These reforms introduced a new public administration paradigm that emphasised the reduction of the role of the state in service delivery, encouraged the deregulation of public enterprises and sought to reduce the scope and cost of government (Economic Commission for Africa 2003). The impact of these reforms on Customs has ranged from: temporary outsourcing of functions to a private sector company in Angola and Mozambique (Moïsé • 2005) awarding of contracts to pre-shipment inspection (PSI) companies to verify the price, quantity and • quality of imported goods for the purpose of preventing capital flight, commercial fraud and duty evasion, which had been implemented in 30 countries 1 (WTO 1996) transformation of the organisation into a semi-autonomous government agency outside the civil • service as happened in Ghana in 1986 (Kusi 1998) and Ethiopia in 1997(Ethiopian Customs Authority 2008 International Network of Customs Universities placement of Customs in semi-autonomous revenue agencies, as has happened in Botswana, Gambia, • Kenya, Lesotho, Malawi, Mauritius, Mozambique, Rwanda, Sierra Leone, South Africa, Swaziland 2 , Tanzania, Uganda, Zambia and Zimbabwe transformation of Customs within government, as has happened in Senegal. • There is considerable analysis on the outsourcing of Customs operational management in Mozambique.…”
Section: A Introductionmentioning
confidence: 99%